Indirect evaluation of digestive tract function on male lambs and ram based on feed digestibility and eating behavior - Prima, A.; Rianto, E.; Purbowati, E.; Purnomoadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
This studywasaimed to examine the development and function ofdigestive organsof lamb in digesting feed based on feed digestibility valueandeating behaviour. The materials used were 11 lambs aged 3-4 months, body weight(BW)14.78 ± 1.99 kg (CV 3.98%), and 11 ramsaged 10-12 months, BW 22.18 ± 1.81 kg (CV 3.29%). The study used a completelyrandomized design of 2x2 in nestedpatterns. There were two ages compared (lambs vs ram) and every age was nested the diet i.e.100%Napiergrass (G100) vs mixed pellet 50% grass and 50% concentrate(G50C50). The diet was given at 3.5% of BW. Parameters observed were dry matter intake(DMI)and digestibility, eating and ruminating time. The results showed that were no significant differences between lambs and rams in DMI (averaged 3.33% BW),digestibility (averaged 49.00%), eating (192.56 min/d), and ruminating (364 min/d). Animalsgiven diet G50C50 had higher (P<0.05) DMI (666 vs 565 g/d), digestibility (50.49%vs 47.53%), and less (P<0.05) eating (47 vs 338 min/d) and ruminating (305 vs 423 min/d), as compared withthose fed diet G100.It is concludedthat the digestive tracts of lambs had developed and function to the stage similar to ram.